SIRT1–SIRT7 in Diabetic Kidney Disease: Biological Functions and Molecular Mechanisms - Qi, Wenxiu; Hu, Cheng; Zhao, Daqing; Li, Xiangyan (Frontiers in Endocrinology, 2022)
Diabetic kidney disease (DKD) is a severe microvascular complication in patients with diabetes and is one of the main causes of renal failure. The current clinical treatment methods for DKD are not completely effective, and further exploration of the molecular mechanisms underlying the pathology of DKD is necessary to improve and promote the treatment strategy. Sirtuins are class III histone deacetylases, which play an important role in many biological functions, including DNA repair, apoptosis, cell cycle, oxidative stress, mitochondrial function, energy metabolism, lifespan, and aging. In the last decade, research on sirtuins and DKD has gained increasing attention, and it is important to summarize the relationship between DKD and sirtuins to increase the awareness of DKD and improve the cure rates. We have found that miRNAs, lncRNAs, compounds, or drugs that up-regulate the activity and expression of sirtuins play protective roles in renal function. Therefore, in this review, we summarize the biological functions, molecular targets, mechanisms, and signaling pathways of SIRT1–SIRT7 in DKD models. Existing research has shown that sirtuins have the potential as effective targets for the clinical treatment of DKD. This review aims to lay a solid foundation for clinical research and provide a theoretical basis to slow the development of DKD in patients.